University transformation towards a learning experience facing the world of work and industry - Elta Sonalitha; Dyah Setyawati; Sugeng Haryanto (University of Merdeka Malang, 2021)
The beginning of this major change was the existence of a very large gap between the output of university graduates and the need for experts in the business and industrial world so that various forms of MBKM activities were projected to provide real contextual experiences that could increase competence, prepare well to enter the world of work and industry, and create new jobs. One of the MBKM programs with the greatest possibility according to competency linearity is the Certified Independent Study and Internship Program (MSIB), where students go directly to the world of work and learn according to their competencies based on experience in the field or project-based learning. The methodology of this research is descriptive qualitative, with the entire population of the University of Merdeka Malang academic community, MSIB participants, and stakeholders in the MSIB Program. Data were obtained through questionnaires, interviews, and Forum Group Discussion. Some of the measurable results include the impact of the implementation of the MSIB program having a good perception at Merdeka University Malang, students have high motivation and interest in implementing the MSIB program, the MSIB program has a direct influence as evidenced by the assessments given by lecturers and students' perspectives on themselves. The results obtained from the implementation of the MSIB Program provide real contextual experiences that can increase competence, prepare well to enter the world of work and industry, as well as the ability create new jobs.